2016
DOI: 10.6065/apem.2016.21.3.143
|View full text |Cite
|
Sign up to set email alerts
|

The cutoff values of indirect indices for measuring insulin resistance for metabolic syndrome in Korean children and adolescents

Abstract: PurposeThe prevalence rates of metabolic syndrome (MetS) and percentile distribution of insulin resistance (IR) among Korean children and adolescents were investigated. The cutoff values of IR were calculated to identify high-risk MetS groups.MethodsData from 3,313 Korean subjects (1,756 boys and 1,557 girls, aged 10–18 years) were included from the Korean National Health and Nutrition Examination Survey conducted during 2007–2010. Three different sets of criteria for MetS were used. Indirect measures of IR we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…The effectiveness of the TyG index for detecting IR has been widely proved in studies of adults from different ethnic groups , but paediatric studies are scarce . The paediatric efficacy of the TyG index, in comparison with the euglyceamic‐hyperinsulinemic clamp, has only previously been evaluated by Mohd et al in obese adolescents .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of the TyG index for detecting IR has been widely proved in studies of adults from different ethnic groups , but paediatric studies are scarce . The paediatric efficacy of the TyG index, in comparison with the euglyceamic‐hyperinsulinemic clamp, has only previously been evaluated by Mohd et al in obese adolescents .…”
Section: Discussionmentioning
confidence: 99%
“…These findings supported the evidence about the complexity of physiological changes during puberty. Furthermore, a study of Korean children aged 10–18 years by Kim et al , found that, when it came to recognising IR in children, the AUC of the TyG index was higher than the AUC of the HOMA‐IR finding, suggesting that when determining the metabolic risk, the TyG index could be more useful than the HOMA‐IR. Our findings, which showed an increasing trend of the TyG index throughout different weight status and pubertal stages, were consistent with the above‐mentioned reports.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data are reported in pediatric age, in which the TyG index has been described as a useful predictor of metabolic abnormalities in Asian, Mexican American, Non-Hispanic White adolescents (15)(16)(17)(18)(19)(20)(21). Untill now there is no consensus for reference criteria in Caucasian children, besides no pediatric study has been conducted on this topic.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Veira Ribeiro et al (31) reported that the cutoff point with the best balance between sensitivity and specificity values was 7.88. A study carried out with Korean adolescents aged 10-18 identified cutoff points between 8.41 and 8.66 for TyG index to predict metabolic syndrome, using different diagnostic criteria (18). Angoorani et al (19) The present study in Caucasian subjects identified an optimal cut-off of 7.98 for IR, that may be used for assessing IR and associated metabolic risk in children and teenagers with overweight and obesity, although caution is required when applied to other populations metabolically at risk.…”
Section: Correlation Between Tyg and Homa-irmentioning
confidence: 99%
“…5The use of HOMA-IR in routine clinical diagnosis has allowed observing that reference values range from 2.6 to 3.8 in adult and pediatric populations in different regions of the world (6-9); therefore, determining reference values for specific populations is highly suggested. (10)(11)(12)(13) The state of Chiapas has a total population of 5 217 908 inhabitants, of whom 74.7% live in poverty and 33.5% lack access to health services. (14,15) Regarding overweight and obesity, a combined prevalence in adolescents from urban areas of the state of 33% has been reported (16), with a HOMA-IR range for the capital between 0.4-7.5 and 21% in obese adolescents.…”
Section: Introductionmentioning
confidence: 99%